DEKONTRUKSI PEMIKIRAN IBNU KHALDUN TENTANG PENDIDIKAN - Burhanuddin, Hamam; Burhanuddin, Hamam (EDUKASI: Jurnal Pendidikan Islam, 2015)
Ibn Khaldun was a gifted philosopher of history and the greatest scholars of his time, one of the leading thinkers ever born. He was a founder of the science of sociology which typically distinguishes the way it treats history as a science and provides reasons to support real events. Tradition survey of scientific conducted by Ibn Khaldun began using tradition to think scientifically and to critique the way of thinking " old model "and the works of former scientists, the results of the investigation regarding previous works, has contributed to the academic to the development of science valid, knowledge ilmiah authentic knowledge. This study focus on Decontruction of Ibn Khaldun education thinking, According Ibn Khaldun science education is not an activity solely is thought and contemplation away from the pragmatic aspects in life, but science and education is nothing but a social phenomenon that is characteristic of the human species. Implication of the study is relevaation in the education modern era.